Program evaluation: Impact of study activities and appreciation of Indonesian exemplary student leadership (SAKTI) at SMP Labschool Cibubur - Rismayati, Ade Imas; Komarudin, Ukim; Maryani, Tri; Bawati, Astuti Tri; Achmad, Satria Keitaro (Jurnal Konatif: Jurnal Ilmiah Pendidikan, 2024)
The Study and Appreciation of Indonesian Exemplary Student Leadership (SAKTI) activity is one of the flagship activities of SMP Labschool Cibubur to prepare students to become leaders. SAKTI activities are activities that are carried out to form positive characters in students. This study aims to determine the impact of this activity on the students of Cibubur Labschool Junior High School. The research, which was carried out at SMP Labschool Cibubur in the first semester of the 2022/2023 school year, used a survey method to collect data on the population of grade VIII students totaling 225 students. Relying on the CIPP evaluation model as the theoretical basis, the researcher uses descriptive analysis of the data. The program evaluation research that has been carried out shows that the implementation of SAKTI has proven to be effective. This can be reviewed from several aspects, namely: in the context of SAKTI activities are carried out based on the goal of achieving the school's vision and the implementation of the P5 Independent Curriculum as a demand for achieving the character of students. In terms of input or input, data was obtained that 90% of students stated that they were ready to participate in activities and receive SAKTI 2022 materials. In terms of the process of this activity, the achievement of the activity process is in the appropriate and very appropriate category, so that it shows the optimal achievement of all the indicators set. From this study, it was also found that SAKTI activities have a positive impact on students' independence and discipline, basic skills, sense of patriotism and nationalism, faith and piety to God Almighty, willingness to share, leadership attitude, and social sensitivity.